Dangerous boobies : breaking up with my time-bomb breasts - Brodnick, Caitlin (Seal Press, 2017)
"After watching too many family members die of cancer, at age 28, public speaker and comedian Caitlin Brodnick was tested for the BRCA1 gene mutation and tested positive, indicating an 87% chance she'd likely be diagnosed with breast cancer in her lifetime. She had a preventative double mastectomy, thereby becoming an everywoman's Angelina Jolie. Dangerous Boobies: Breaking Up with My Time-Bomb Breasts goes in depth into her experience from testing to surgery and on to recovery. With a warm, funny, and approachable voice, Caitlin tells readers the full story, even sharing what it was like to go from a size 32G bra--giant, for a woman who is barely over five feet tall!--to a 32C. Engaging and open, she admits to having hated her breasts long before her surgery, and enjoying the process of "designing" her new breasts, from the shape of the breasts to the size and color of the nipples. While Caitlin's primary narrative explores the BRCA gene and breast cancer, her story is also one about body acceptance and what it takes to be confident with and in charge of one's body. Her speaking engagements and comedy routines have shown that the wider topic of breasts, breast size, and personal identity is resonating with younger readers"--